Estimation of Producers’ Surplus of Large Cardamom in Arunachal Pradesh: A Value Chain Mapping - Singh, Ram; Singh, N. Anand Kumar; Devi, L. Geetarani; Feroze, S.M.; Chiphang, S.; Kumar, Shiv (Indian Journal of Extension Education, 2021)
Study was conducted in Anjaw district of Arunachal Pradesh to find out producers’ surplus of large cardamom in the state of Arunachal Pradesh. The channel-I (Producer → Primary wholesaler → Secondary wholesaler/ trader → Retailer → Consumer) was found to be pivot channel which was preferred by 84 per cent of respondents. Although chain is long this may reduce the share of producers’ in consumers’ rupee. The marketable surplus (97.62%) was observed to be more than marketed surplus (96.90%) at margin level, indicates no distress sale of the produce in the study area. Hence, there is a scope of opening market yards at cluster of villages basis for purchasing of produce from the producers. The losses incurred at farmers’ field and during the marketing of the produce were main concern and it necessitates for research and development to reduce the losses through intervention of scientific storage as well as trainings of the farmers on packaging of the produce. Hence, many opportunities like opening market yards, establishment of storage with its training to youth would help in livelihood and income generation of not only the producer but also to other unemployed youths. Hence, these identified opportunities needed to tap in the state of Arunachal Pradesh.
Keywords: Producers; Surplus; Large cardamom; Value chain; Map; NEHR